ANALISIS PROSES LELANG YANG DIAJUKAN KREDITUR DARI OBJEK HAK TANGGUNGAN BERDASARKAN PUTUSAN NOMOR 427/PDT.G/2022/PN.BKS - NIM. A1011201293, WILDAN MAULANA RAMADHAN (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT Auctions have an important role in selling mortgage objects. Mortgage objects can be auctioned to pay off obligations guaranteed by mortgage rights. In the case position, we will discuss the issue of auctions below the limit on mortgage objects belonging to Katasha Nabila Ratri. Katasha Nabila Ratri, as the debtor, is disputing 2 plots of land that are the object of her mortgage which are registered as objects of collateral. The title of this research is Analysis of the Auction Process Proposed by Creditors for Mortgage Objects Based on Decision Number 427/Pdt.G/2022/PN.Bks, the problem formulation is